The Asymptotic Binary Goldbach and Lemoine Conjectures : Binary Goldbach and Lemoine Conjectures - Agama, Theophilus; Gensel, Berndt (My University, 2022)
In this paper we use the former of the authors developed theory of circles of partition to investigate possibilities to prove the binary Goldbach as well as the Lemoine conjecture. We state the squeeze principle and its consequences if the set of all odd prime numbers is the base set. With this tool we can prove asymptotic versions of the binary Goldbach as well as the Lemoine conjecture.
Keywords: axes; squeeze principle